0695 Objectively Measured Total Sleep Time as a Tool to Detect Longitudinal Changes In Alzheimer's Disease Neuroimaging Biomarker (FDG PET). (27th April 2018) - Sharma, R A; Miller, M D; Kam, K; Parekh, A; Bubu, O M; Rivas, J; Ayappa, I; Rapoport, D M; Varga, A W; Osorio, R S
Abstract: Introduction: The use of neuroimaging techniques such as FDG PET to identify early Alzheimer's disease (AD) pathology as predictor of subsequent neurodegeneration has been pivotal in AD research. Moreover, recent literature suggests that sleep disruption and obstructive sleep apnea (OSA) are risk factors for AD, contributing to AD specific neurodegeneration. However, relationship between objective measure of sleep and neuroimaging markers of AD are not well established. Our objective is to look for associations between baseline total sleep time (TST) measured by actigraphy and AD specific reduction in cerebral metabolism as measured by FDG PET longitudinally. Methods: All subjects completed 1-week of actigraphy. FDG-PET scans were done following standardized procedures. Only 14 subjects completed follow-up FDG PET scan (2.31 ± .43 years) later. Subjects with AHI4%≥ 15 were excluded from the analysis. AD FDG mask was created for PET data using standard Meta-ROI SUVR of cortical regions of the brain that are sensitive for AD. Partial correlations were corrected for age, gender, ApoE4. Results: Our cohort consisted of 34 cognitively normal (CDR=0, MMSE= 29.19±.98) elderly (67.73 ± 6.83 years), 63.9% were female and 38.9% were ApoE4 positive. A significant positive association was found between objective TST and AD FDG mask at cross-sectional analysis on partial correlation after controlling for covariates (r=0.35, p=0.04). Additionally, significant associations were also observed between baseline TST and Delta AD FDG mask after controlling for covariates (r=0.82, p=0.002). Conclusion: Objectively measured decreased TST is correlated with decreased cerebral metabolism in AD specific regions even after controlling for confounders at cross-sectional analysis. Interestingly lower TST at baseline also predicted future decline in cerebral metabolism on AD FDG mask over the 2 year follow-up period. Our findings suggest that decreased TST in cognitively normal elderly may predispose them to AD pathogenesis as confirmed by FDG PET, however the causal association should be interpreted with caution as sleep disturbances can be an early symptom of preclinical AD. Sleep hygiene and interventions might be beneficial in mitigating the Alzheimer's disease process. Support (If Any):